Self-Rated Health Among Very Old People in European Countries: An Explorative Study in Latvia and Sweden. (31st July 2015) - Harschel, Anne K.; Schaap, Laura A.; Iwarsson, Susanne; Horstmann, Vibeke; Tomsone, Signe
Objectives: To explore and gain insight into factors related to self-rated health (SRH) among very old people in two European countries.Methods: The study was based on Latvian ( n = 301) and Swedish ( n = 397) data from the baseline of the Enabling Autonomy, Participation, and Well-Being in Old Age: The Home Environment as a Determinant for Healthy Ageing Survey Study. Besides descriptive statistics, ordinal regression analysis was used to analyze demographic, physical and mental health-related, functional and environmental factors related to SRH in each sample.Results: In both samples, participants with worse perceived physical mobility and more symptoms were significantly more likely to have worse SRH. There were more diverse results regarding other factors in terms of opposite relations to SRH, comparing the two samples.Discussion: Preventive measures and health care should focus on improving and supporting mobility and physical health among older people. Especially in countries with low scores on indicators of health such as Latvia, to minimize health inequalities. More attention should be paid to factors to improve the general health status of the population.